Historical Linguistics 2001 : Selected Papers from the 15th International Conference on Historical Linguistics, Melbourne, 13-17 August 2001 - Blake, Barry J.; Burridge, Kate; Taylor, Jo, 1964- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2003)
This is a selection of papers from the 15th International Conference on Historical Linguistics held in Melbourne 13-17 August 2001, hosted by the Linguistics Program at La Trobe University. The papers range from the general theoretical to the study of particular languages and embrace most areas of linguistics, particularly morpho-syntax.